Fitoekstrasi Merkuri dari Tanah Tercemar Limbah Tambang Emas Skala Kecil dan Pengaruhnya pada Pertumbuhan Tanaman Jagung - Nurul Muddarisna; B.D. Krisnayanti; E. Handayanto (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
In West Lombok, gold amalgamation tailings are commonly discharged to agricultural lands resulting in reduced maize yield in the area. Phytoremediation can represent a low-cost alternative to traditional techniques such as soil removal. This study was aimed to elucidate the potential of Lindernia crustacea (L.) F., Paspalum conjugatum L., and Cyperus kyllingia Endl., for phytoremediation of mercury-contaminated soils in conjunction with the ammonium thiosulphate to phytoextract mercury and its effect on maize growth. Each of the plant seedlings was planted in a plastic pot containing 15 kg of mercury-contaminated soil for 9 weeks. Treatments tested were three plant species), and two rates of ammonium thiosulphate application, i.e. 0 and 8 g / kg of soil. Ammonium thiosulphate was applied one week before harvesting the plants. At harvest (9 weeks) shoots and roots were analyzed for mercury concentration. The remaining soils in the pots were used to grow maize for 8 weeks. The results showed that on average, the addition of ammonium thiosulphate increased the accumulation of mercury in plant shoots and roots by 82% and 47%, respectively, compared to the media without addition of ammonium thiosulphate. In comparison to the control treatment, the average increase of dry weight of maize (shoot+root) grown on media previously remediated with three plant species with addition of ammonium thiosulphate was 40%, while that grown on media previously remediated with three plant species without addition of ammonium thiosulphate was 62%.